2015
DOI: 10.5433/1679-0359.2015v36n5p3161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the association of diet, omega-three, and antioxidants in dogs with chronic kidney disease

Abstract: To evaluate the contribution of the drug combination of omega-3, vitamin E, sodium selenite, copper gluconate, zinc gluconate, chondroitin sulfate, and glucosamine (Gerioox ® ), 12 dogs with chronic kidney disease (CKD) in outpatient clinical care at the veterinary hospital of a federal institution of higher education were studied. Complete blood counts, urinalyses, measurements of the serum concentration of calcium, phosphorus, urea and creatinine, and calculations of the urinary protein to creatinine ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Dietary n-3 FA supplementation in renal insufficiency dogs lead to significant reduction in BUN and triglycerides . A study conducted by Valle et al, (2015) showed significant increase in GFR and decrease in creatinine level after supplementation of renal feed with omega-3 and antioxidants. These also prevent the progression of chronic renal failure (CRF) due to its action on the abnormalities (lipid and immune) that are secondary to CRF.…”
Section: Omega-3 Fa and Renal Healthmentioning
confidence: 99%
“…Dietary n-3 FA supplementation in renal insufficiency dogs lead to significant reduction in BUN and triglycerides . A study conducted by Valle et al, (2015) showed significant increase in GFR and decrease in creatinine level after supplementation of renal feed with omega-3 and antioxidants. These also prevent the progression of chronic renal failure (CRF) due to its action on the abnormalities (lipid and immune) that are secondary to CRF.…”
Section: Omega-3 Fa and Renal Healthmentioning
confidence: 99%
“…A creatinina sérica, a excreção de sódio e a ureia nitrogenada no sangue foram verificados no trabalho de Javedan et al (2016) como marcadores de lesão renal, onde o ácido linoleico conjugado (CLA) diminuiu os níveis dos mesmos. O uso de proteína de alto valor biológico também contribui para a redução da formação de ureia e um aumento da ureia pode ser devido à sua produção como uma pior excreção que pode estar relacionada à baixa taxa de filtração glomerular (VALLE et al, 2015).…”
Section: Avaliação Do Hemograma E Leucograma Das Matrizes De 34 a 190unclassified